DNA libraries for the construction of phage libraries: statistical and structural requirements and synthetic methods - Lindner, Thomas; Kolmar, Harald; Haberkorn, Uwe; Mier, Walter (Molecules, 2011)
Peptide-based molecular probes identified by bacteriophage (phage) display technology expand the peptide repertoire for in vivo diagnosis and therapy of cancer. Numerous peptides that bind cancer-associated antigens have been discovered by panning phage libraries. However, until now only few of the peptides selected by phage display have entered clinical applications. The success of phage derived peptides essentially depends on the quality of the library screened. This review summarizes the methods to achieve highly homogenous libraries that cover a maximal sequence space. Biochemical and chemical strategies for the synthesis of DNA libraries and the techniques for their integration into the viral genome are discussed in detail. A focus is set on the methods that enable the exclusion of disturbing sequences. In addition, the parameters that define the variability, the minimal numbers of copies per library and the use of alternating panning cycles to avoid the loss of selected hits are evaluated.